Relapse risk after autologous stem cell transplantation in patients with lymphoma based on CD34+ cell dose. Issue 4 (3rd April 2017) - Sorigue, Marc; Sancho, Juan-Manuel; Morgades, Mireia; Moreno, Miriam; Grífols, Juan-Ramon; Alonso, Eva; Juncà, Jordi; Ferrà, Christelle; Batlle, Montserrat; Vives, Susana; Motlló, Cristina; García-Caro, Montserrat; et al.
Abstract: It is unclear whether higher CD34 + cell doses infused for ASCT have any influence on survival or relapse in patients with lymphoma. We analyzed the correlation of infused CD34 + cell dose with relapse, survival, and hematopoietic recovery in 146 consecutive patients undergoing ASCT for lymphoma. Higher doses (>5 × 10 6 /kg) were significantly correlated with earlier hematopoietic recovery, fewer infectious episodes, lower transfusion needs. No differences were observed in lymphoma outcomes (4-year relapse incidence of 38% [95%CI: 29%–48%] in the lower dose group versus 51% [95%CI: 30%–69%] in the higher dose group, 10-year OS probabilities of 58% [95%CI: 48%–68%] versus 75% [95%CI: 59%–91%], 10-year DFS probabilities of 47% [95%CI: 37%–57%] versus 42% [95%CI: 23%–61%], p = NS for all outcomes). In this series, a higher infused CD34 + cell dose did not correlate with survival or relapse but correlated with earlier hematopoietic recovery and lower resource consumption.